PENGALAMAN BERMAIN SAAT TERJADI INTERAKSI DALAM TEAM-BASED MOBILE GAME - Setyowulan, Amalia (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
Interaction cannot be separated from everyday human life, because human cannot live by themselves. Interaction always happens anywhere and anywhere in the video game world without exception, especially online video games that connect several players at once. With the development of technology, online gaming can be played not only on computers but can also be played on the go on a smartphone. By connecting several players online via smartphones, there is an interaction between players in a video game. Video games with interactions are mainly in team-based format. Many factors influence interactions in the video game, such as interactions that occur between one player and other players and the interaction between players and features in the video game. Based on this, the researchers wish to examine further the experience formed through the interactions that exist in the video game, and their relation to the player's interest in the video game being played. This study uses quantitative methods, including quasi experiments. The treatment in the experiment is to condition the subjects to play in groups (team-based mobile game) so that interactions occur. The research subjects were not gender limited, with players ranging in age from 17 to 23 years old. Data is collected using questionnaires. In interactions that occur, a playing experience is formed, through reactions of supporting one another. The result shows that interaction in team-based mobile video games give rise to playing experience that affects pleasure, and interest in continuing the gaming activity. Interaksi tidak dapat dipisahkan pada kehidupan manusia sehari-hari, karena manusia tidak bisa hidup dengan bergantung pada diri sendiri. Interaksi selalu terjadi dimanapun dan kapanpun tidak terkecuali dalam dunia game terutama game online yang menghubungkan beberapa pemain sekaligus. Dengan perkembangan teknologi game online dapat dimainkan tidak hanya pada komputer namun dapat juga dimainkan secara mobile menggunakan smartphone. Dengan terhubungnya beberapa pemain game secara online melalui smartphone, maka terjadi sebuah interaksi antar pemain dalam sebuah game. Game yang terdapat interaksi di dalamnya terutama ada pada game dengan format team-based. Banyak faktor yang mempengaruhi terjadinya interaksi di dalam game tersebut, seperti interaksi yang terjadi antara satu pemain dengan pemain lainnya serta interaksi pemain dengan  fitur di dalam game. Dengan berlandaskan hal tersebut, peneliti ingin meneliti lebih dalam bentuk interaksi yang ada dalam game dan kaitannya dengan ketertarikan utama pemain pada game yang dimainkan. Penelitian ini menggunakan metode kuantitatif yang diikuti dengan eskperimen, dengan menggunakan kuisioner yang melibatkan subyek penelitian yang tidak terbatas gender, dengan rentang usia pemain antara 17 sampai 23 tahun. Dari interaksi yang terjadi terbentuk sebuah pengalaman bermain, sehingga mendukung satu sama lain. Dua dari lima pengalaman bermain yang ada mendominasi dan menunjukkan ketertarikan pemain terhadap game yang dimainkan.Kata kunci: game mobile, interaksi, pengalaman bermain.